PROSES SCAFFOLDING BERDASARKAN KESALAHAN PESERTA DIDIK DALAM PEMECAHAN MASALAH VOLUME BENDA PUTAR - Fahcruddin, Imam; Sulandra, I Made (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
One of the applied integral is calculating the volume of a solid of revolution. Some errors experienced by students when solving the problem of volume of a solid of revolution are errors in drawing rotating objects and errors in formulating the volume of rotating objects in the form of integrals. This study aims to determine the scaffolding process that is given to students based on errors experienced when resolving rotating objects volume problems. The selection of research subjects is based on the smooth communication and ability of students so as to get three people. The data collection technique used is think aloud. From the results of the study obtained several errors experienced by the three research subjects with different initial abilities that is to simplify the function of absolute value. Scaffolding that is applied is to provide questions that lead to remember and explain the definition of an absolute value function. In addition, all research subjects also experienced errors in formulating the volume of solid of revolution. The scaffolding that is applied is to provide questions to remind about the concepts used in formulating the volume of solid of revolution. Then, the research subject with low ability has an error in determining the area that is limited by several functions and an error in identifying the components used to determine the volume of solid of revolution. Scaffolding applied is inviting students to contribute to look for clues in determining areas that are limited by several functions.